Enhancing long-term sustainability of ICT-driven public open spaces in Shanghai, China through optimizing stakeholder conflicts - Chen, Shaohan (2024)
The integration of ICT-driven sustainable practices in public open spaces (IDS-POS) offers significant opportunities for enhancing urban sustainability. However, during the operation and management of IDS-POS projects, i.e., the post-construction stage, stakeholder conflicts that can jeopardize long-term sustainability are often encountered, and limited attention has been given to understanding and managing these conflicts. This study aims to address this gap by investigating the mechanisms through which stakeholders collaborate and conflict over the policy and sustainability benefits of IDS-POS during the post-construction stage, identifying specific conflict issues, and proposing robust conflict optimization strategies. The three IDS-POS projects in Shanghai, China were used as the study areas. Employing a mixed-methods approach, the study first conducted a questionnaire survey, collecting 481 valid responses from stakeholders involved in IDS-POS projects. Structural Equation Modeling and fuzzy set Qualitative Comparative Analysis were used to analyze the quantitative data. Subsequently, expert focus group discussions were held, utilizing the Theory of Inventive Problem Solving to interpret specific conflict issues, propose optimization strategies, and validate their robustness through Fuzzy Comprehensive Evaluation. The findings reveal that ICT-driven environmental sustainability and policy governance significantly promote stakeholder value co-creation, which in turn enhances the long-term sustainability of IDS-POS projects but also intensifies conflicts that constrain the sustainability of IDS-POS. 20 specific conflict issues across environmental, economic, social, and governance domains were identified, each exerting varying degrees of impact on sustainability outcomes of IDS-POS, with policy governance and social conflicts emerging as the most critical barriers. The study developed and validated 34 targeted conflict optimization strategies. The strategies were clustered into four comprehensive pathways that address specific issues, even in the absence of prior project experience. This study contributes to the conflict management and urban sustainability literature by introducing a systematic “problem identification-analysis-solution-evaluation” framework through a synthesis of mixedmethods approach and complementary analytical techniques. The study findings provide certain implications for practitioners involved in urban development projects characterized by high stakeholder diversity and complexity.